The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2147/ijgm.s273807
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence and Risk Factors for Diabetic Peripheral Neuropathy Among Saudi Hospitalized Diabetic Patients: A Nested Case-Control Study</p>

Abstract: Objective: To determine the prevalence and the risk factors of diabetic peripheral neuropathy (DPN) in hospitalized adult Saudi diabetics. Methods: This is a retrospective, nested case-control study conducted at King Abdulaziz Medical City (KAMC) in Riyadh, Saudi Arabia. All diabetic patients admitted to the hospital between the January 1, and December 31, 2018 were considered for inclusion in the study. Patients with DPN were identified and three controls per case were randomly selected from the remaining dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…A recent study was performed among Hospitalized Diabetic Patients in Riyadh, Saudi Arabia and they found that only 3.5% of them had DPN. It is noticed that the reported prevalence of DPN is decreasing throughout the years; this might be due to the increase in the awareness of patients about glycemic control, which is a crucial factor in delaying the rate of development of DPN [21]. However, this disparity in prevalence could be due to the difference in populations and the methods of data collection since some studies have used clinically based methods for the diagnosis, while others like this one have used questionnaire-based methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study was performed among Hospitalized Diabetic Patients in Riyadh, Saudi Arabia and they found that only 3.5% of them had DPN. It is noticed that the reported prevalence of DPN is decreasing throughout the years; this might be due to the increase in the awareness of patients about glycemic control, which is a crucial factor in delaying the rate of development of DPN [21]. However, this disparity in prevalence could be due to the difference in populations and the methods of data collection since some studies have used clinically based methods for the diagnosis, while others like this one have used questionnaire-based methods.…”
Section: Resultsmentioning
confidence: 99%
“…This might be because the doctors were not aware of the DPN or they have considered it as part of the regular progression and the natural history of diabetes and not as a complication, this might indicate a lack of awareness among doctors about DPN, which will require serious intervention to raise their awareness about this issue. One of the limitations of this study is that it did not investigate the presence of risk factors for DPN among the participants, risk factors such as BMI, poor glycemic control, and other comorbidities (dyslipidemia, peripheral vascular disease, hypertension, and chronic kidney disease), have been significantly associated with DPN [21]. Another limitation is that only a questionnaire-based assessment for DPN was made and was not combined with clinical assessment.…”
Section: Resultsmentioning
confidence: 99%
“…Changes of plasma concentration and structural modi cation of albumin induced by high glucose or free radicals impair its antioxidant properties and aggravate oxidative stress [19]. Several previous studies have explored the association of serum albumin with the development of DPN, and provided inconsistent results [12][13][14][15]. Iwasaki et al reported that serum albumin was independently related to the median motor nerve conduction velocity and minimum F-wave latency in 130 Japanese patients with T2DM, and was signi cantly inversely associated with the presence of DPN [12].…”
Section: Discussionmentioning
confidence: 99%
“…Data from a cross-sectional study of 409 Chinese patients with T2DM underwent measurement of nerve conduction (NC) showed that serum albumin was independently associated with peripheral nerve function as re ected by composite Z scores of all NC parametersin T2DM patients, especially in those with albuminuria [13]. Recently reported data from the Saudi study, which included 2,906 hospitalized adult diabetics, demonstrated that DPN cases had a signi cantly lower serum albumin levels compared with those without DPN [14]. However, no statistically signi cant association between serum albumin and DPN in US patients undergoing foot and ankle surgery with a history of Type 1 and 2 diabetes mellitus over a 13 month period [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation